Clear cell renal cell carcinoma: validation of World Health Organization/International Society of Urological Pathology grading. Issue 6 (2nd October 2017) - Dagher, Julien; Delahunt, Brett; Rioux‐Leclercq, Nathalie; Egevad, Lars; Srigley, John R; Coughlin, Geoffrey; Dunglinson, Nigel; Gianduzzo, Troy; Kua, Boon; Malone, Greg; Martin, Ben; Preston, John; et al.
Abstract : Aims: In 2012, the International Society of Urological Pathology (ISUP) introduced a novel grading system for clear cell renal cell carcinoma (ccRCC) and papillary renal cell carcinoma. This system is incorporated into the latest World Health Organization renal tumour classification, being designated WHO/ISUP grading. This study was undertaken to compare WHO/ISUP and Fuhrman grading and to validate WHO/ISUP grading as a prognostic parameter in a series of clear cell RCC. Methods and results: Analysis of 681 cases of ccRCC showed that 144 tumours could not be assigned a Fuhrman grade on the basis of ambiguous grading features. The application of WHO/ISUP grading resulted in a general down‐grading of cases when compared with Fuhrman grading. In a sub‐group of 374 cases, for which outcome data were available, 9.3% were WHO/ISUP grade 1, 50.3% were grade 2, 24.1% grade 3 and 16.3% grade 4, while the distribution of Fuhrman grades was 0.4% grade 1, 48.7% grade 2, 29.4% grade 3 and 21.5% grade 4. There were no recurrence/metastases amongst patients with WHO/ISUP grade 1 tumours and there was a significant difference in outcome for WHO/ISUP grades 2, 3 and 4. For Fuhrman grading the cancer‐free survival was not significantly different for grade 2 and grade 3 tumours. On multivariate analysis WHO/ISUP grade and pT staging category were found to retain prognostic significance. Conclusions: The study demonstrates that FG cannot be applied in >20% of cases of ccRCC and the WHO/ISUP provides superior prognostic information.